Exploring employee performance determinants at Pulang Pisau District Education Office: Work environment, discipline, and experience - Talenta R, Fetra (Indonesian Journal of Educational Management and Leadership, 2024)
Purpose− The primary objective of this research is to investigate and elucidate the combined influence of work climate, work discipline, and work experience on employee performance, as well as the individual impacts of work climate, work discipline, and work experience on employee performance. Method− This study employed a quantitative research approach, specifically utilizing a multiple linear regression model. The research population consisted of 57 employees from the Pulang Pisau District Education Office, and the sampling method employed was total sampling. Data collection was conducted through the distribution of questionnaires, and the validity and reliability of the questionnaire measurements were assessed. Hypothesis testing was performed using multiple regression analysis techniques. Findings− The findings of the research demonstrate that work climate, work discipline, and work experience collectively and individually exert a positive and significant influence on employee performance at the Pulang Pisau District Education Office. Specifically, the analysis revealed: (1) a significant positive relationship between work climate, work discipline, and work experience collectively and employee performance, (2) a significant positive association between work climate and employee performance, (3) a notable positive influence of work discipline on employee performance, and (4) a significant positive impact of work experience on employee performance at the Pulang Pisau District Education Office.